PENERAPAN PEMBELAJARAN KOOPERATIF NUMBER HEAD TOGETHER (NHT) UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA KELAS VIII SMP IT SUHADAH YOGJAKARTA - Mariamah, Mariamah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2014)
This study aims to determine the ability of communication mathematics students in grade VIII SMP IT Suhadah Yogyakarta through cooperative learning type Number Head Together (NHT). This study is a classroom action research. The instrument used to collect data is a test instrument. The results of the research for the students' communication ability aspects improved from cycle I of cycle II for each aspect: the first aspect is illustrating mathematical ideas from 30% to 47%, an increase of 17%. The second aspect describes the answer and the use of symbols from 20% to 40.5%. The increase is as much as 20.5%. The total achievement for cycle II is 85.7%, which in this case has reached the criteria 85.7%> 85%. We conclude that NHT learning has been effective for students' mathematical communication skills on straight-line equations. In addition, for teacher and student activity, in the first cycle only active categories have increased